Development of flavivirus subviral particles with low cross-reactivity by mutations of a distinct antigenic domain - Tabata, Koshiro; Itakura, Yukari; Ariizumi, Takuma; Igarashi, Manabu; Kobayashi, Hiroko; Intaruck, Kittiya; Kishimoto, Mai; Kobayashi, Shintaro; Hall, William W.; Sasaki, Michihito; Sawa, Hirofumi; Orba, Yasuko (Applied microbiology and biotechnology, 2023)
The most conserved fusion loop (FL) domain present in the flavivirus envelope protein has been reported as a dominant epitope for cross-reactive antibodies to mosquito-borne flaviviruses (MBFVs). As a result, establishing accurate serodiagnosis for MBFV infections has been difficult as anti-FL antibodies are induced by both natural infection and following vaccination. In this study, we modified the most conserved FL domain to overcome this cross-reactivity. We showed that the FL domain of lineage I insect-specific flavivirus (ISFV) has differences in antigenicity from those of MBFVs and lineage II ISFV and determined the key amino acid residues (G106, L107, or F108), which contribute to the antigenic difference. These mutations were subsequently introduced into subviral particles (SVPs) of dengue virus type 2 (DENV2), Zika virus (ZIKV), Japanese encephalitis virus (JEV), and West Nile virus (WNV). In indirect enzyme-linked immunosorbent assays (ELISAs), these SVP mutants when used as antigens reduced the binding of cross-reactive IgG and total Ig induced by infection of ZIKV, JEV, and WNV in mice and enabled the sensitive detection of virus-specific antibodies. Furthermore, immunization of ZIKV or JEV SVP mutants provoked the production of antibodies with lower cross-reactivity to heterologous MBFV antigens compared to immunization with the wild-type SVPs in mice. This study highlights the effectiveness of introducing mutations in the FL domain in MBFV SVPs with lineage I ISFV-derived amino acids to produce SVP antigens with low cross-reactivity and demonstrates an improvement in the accuracy of indirect ELISA-based serodiagnosis for MBFV infections. Key points • The FL domain of Lineage I ISFV has a different antigenicity from that of MBFVs. • Mutated SVPs reduce the binding of cross-reactive antibodies in indirect ELISAs. • Inoculation of mutated SVPs induces antibodies with low cross-reactivity.